At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's solve the equation [tex]\(3^{2x} = 9^{3x - 4}\)[/tex] step-by-step.
First, we know that [tex]\(9\)[/tex] can be written as a power of [tex]\(3\)[/tex]:
[tex]\[ 9 = 3^2 \][/tex]
Substituting [tex]\(3^2\)[/tex] for [tex]\(9\)[/tex] in the original equation, we get:
[tex]\[ 3^{2x} = (3^2)^{3x - 4} \][/tex]
Next, we use the power of a power rule [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ 3^{2x} = 3^{2 \cdot (3x - 4)} \][/tex]
Simplify the exponent on the right-hand side:
[tex]\[ 3^{2x} = 3^{6x - 8} \][/tex]
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ 2x = 6x - 8 \][/tex]
To solve for [tex]\(x\)[/tex], we need to isolate [tex]\(x\)[/tex] on one side of the equation. First, subtract [tex]\(6x\)[/tex] from both sides:
[tex]\[ 2x - 6x = -8 \][/tex]
[tex]\[ -4x = -8 \][/tex]
Next, divide both sides by [tex]\(-4\)[/tex]:
[tex]\[ x = \frac{-8}{-4} \][/tex]
[tex]\[ x = 2 \][/tex]
Therefore, the value of [tex]\(x\)[/tex] that satisfies the equation [tex]\(3^{2x} = 9^{3x - 4}\)[/tex] is [tex]\(x = 2\)[/tex].
So, the answer is:
[tex]\[ \boxed{2} \][/tex]
First, we know that [tex]\(9\)[/tex] can be written as a power of [tex]\(3\)[/tex]:
[tex]\[ 9 = 3^2 \][/tex]
Substituting [tex]\(3^2\)[/tex] for [tex]\(9\)[/tex] in the original equation, we get:
[tex]\[ 3^{2x} = (3^2)^{3x - 4} \][/tex]
Next, we use the power of a power rule [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ 3^{2x} = 3^{2 \cdot (3x - 4)} \][/tex]
Simplify the exponent on the right-hand side:
[tex]\[ 3^{2x} = 3^{6x - 8} \][/tex]
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ 2x = 6x - 8 \][/tex]
To solve for [tex]\(x\)[/tex], we need to isolate [tex]\(x\)[/tex] on one side of the equation. First, subtract [tex]\(6x\)[/tex] from both sides:
[tex]\[ 2x - 6x = -8 \][/tex]
[tex]\[ -4x = -8 \][/tex]
Next, divide both sides by [tex]\(-4\)[/tex]:
[tex]\[ x = \frac{-8}{-4} \][/tex]
[tex]\[ x = 2 \][/tex]
Therefore, the value of [tex]\(x\)[/tex] that satisfies the equation [tex]\(3^{2x} = 9^{3x - 4}\)[/tex] is [tex]\(x = 2\)[/tex].
So, the answer is:
[tex]\[ \boxed{2} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.